Strategy of Using Emotional Factors of Perception in Managing Product Competitiveness - S. A. Afonsky (Вестник Российского экономического университета имени Г. В. Плеханова)
The article highlights the role of emotions as an alternative of behavior research that has already been thoroughly studied. Emotion studies in marketing concern emotional status of both customers and sellers and managers. Emotions become apparent in facial expression, in different gestures and body posture. The author raises questions dealing with emotion origin through agitation, their transformation, interaction between positive and negative emotions. Contrary and mutually complementary emotion status as a result of the same agitation was analyzed. The notion of satisfaction as a key emotion after getting or consuming product or service is discussed. The goal of the article is to show the basis of analyzing emotions, their estimation and to demonstrate how emotions function as irritants and what result can be obtained in influencing customers. As a conclusion the author describes prospects of further investigation aimed at studying emotions in marketing.